2020
DOI: 10.1002/chem.202001762
|View full text |Cite
|
Sign up to set email alerts
|

A “Push–Pull” Stabilized Phosphinidene Supported by a Phosphine‐Functionalized β‐Diketiminato Ligand

Abstract: The use of a bis(diphenyl)phosphine functionalized β‐diketiminato ligand, [HC{(CH 3 )C} 2 {( ortho ‐[P(C 6 H 5 ) 2 ] 2 C 6 H 4 )N} 2 ] − (PNac), as a support for germanium(II) and tin(II) chloride and phosphaketene compounds, is described. The conformational fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 88 publications
1
27
0
1
Order By: Relevance
“…[6] This ability makes phosphaketenes excellent reagents for forming both single and multiple phosphorus À element bonds. [6,7] The generation of the first boron-functionalized phosphaethynolates was reported in 2017, but their definitive isolation and structural confirmation was provided by Goicoechea and co-workers in 2018. [8] Thus far only a handful of boron-functionalized phosphaethynolates/phosphaketenes (i.e.…”
mentioning
confidence: 99%
“…[6] This ability makes phosphaketenes excellent reagents for forming both single and multiple phosphorus À element bonds. [6,7] The generation of the first boron-functionalized phosphaethynolates was reported in 2017, but their definitive isolation and structural confirmation was provided by Goicoechea and co-workers in 2018. [8] Thus far only a handful of boron-functionalized phosphaethynolates/phosphaketenes (i.e.…”
mentioning
confidence: 99%
“…[12] To improve this situation we have recently synthesized germylene E (Figure 1), [13] which is based on the dipyrromethane scaffold,a nd we have already proven that it forms stable d 10 metal derivatives. [13,17] Although two additional metal-free PGeP germylenes have been recently communicated (D and F in Figure 1), germylene D has only been used as al igand in nickel(0) complexes, [14] and no reaction with aT Mc omplex has yet been reported for germylene F. [18] We now report the reactivity of germylene E with the lightest metal dichlorides of groups 8-12 of the periodic table (Fe-Zn). These reactions have afforded stable chloridogermyl PGeP pincer complexes of earth-abundant metalsw hose metal atoms are in unstrained square planar (Fe II ,C o II ,N i II )o rt etrahedral (Cu I ,Z n II )l igand environments.…”
Section: Introductionmentioning
confidence: 78%
“…No single crystals of compound 1 could be obtained, but an X‐ray diffraction (XRD) study on a crystal of compound 2 (data taken at 157 K) revealed that it was constituted by square planar cobalt(II) molecules in which the metal atom is attached to a chloridogermyl PGeP pincer ligand (Figure 2) with a Co−Ge distance of 2.2519(5) Å. This molecule is reminiscent of the only previously known square planar complex derived from germylene E , that is [PdCl{κ 3 P , Ge , P ‐GeCl(pyrmP i Pr 2 ) 2 CMe 2 }], which was prepared by treating the T‐shaped palladium(0) complex [Pd{κ 3 P , Ge , P ‐Ge(pyrmP i Pr 2 ) 2 CMe 2 }] with HCl or, alternatively, by reacting germylene E with [PdCl 2 (MeCN) 2 ] [18] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations